Flexible carbon fiber membrane based on hollow Co / CoP heterostructure and preparation method and application thereof

Through tannin etching and electrospinning technology, the Co/CoP heterostructure and carbon nanofiber were constructed, which solved the conductivity and stability of CoP materials, and achieved excellent HER catalytic performance and high electrical capacity of Co/CoP@CNF Chemical activity.

CN119265798APending Publication Date: 2025-01-07JILIN TEACHERS INST OF ENG & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411227111.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, CoP catalytic materials have challenges in conductivity and stability, and lack Co/CoP heterojunction and hollow structures, affecting the exposure and catalytic properties of their electroactive sites.

Method used

Hollow structures are formed through tannin etching technology, carbon nanofibers are prepared by electrospinning technology, and Co/CoP heterostructure is constructed through heat treatment and phosphating processes, and network structure is formed by combining carbon nanofibers.

Benefits of technology

The excellent HER catalytic performance of Co/CoP@CNF materials was achieved, showing high electrochemical active area and active site exposure, significantly improved stability and conductivity, and improved stability and efficiency of the catalytic process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265798A_ABST
    Figure CN119265798A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure and a preparation method and application thereof, and belongs to the technical field of carbon fiber membrane materials. The method comprises the following steps: firstly, preparing hollow H-ZIF-67; then polyacrylonitrile is added into the hollow H-ZIF-67, and an H-ZIF-67 fiber membrane is prepared through electrostatic spinning; finally, the H-ZIF-67 fiber membrane is placed in a tubular furnace, heating is conducted, and H-Co-coated CNF is obtained; sodium hypophosphite powder is placed on the upstream of a tubular furnace, H-Co (at) CNF is placed on the downstream of the tubular furnace, heating is conducted under argon flow, and the flexible carbon fiber membrane H-Co / CoP (at) CNF based on the hollow Co / CoP heterostructure is obtained. According to the hollow structure and the network structure formed by the carbon nanofibers, the material has a large specific surface area, and due to the combination of the heterostructure Co / CoP and the porous hollow carbon nanofiber structure, the H-Co / CoP-coated CNF shows excellent HER catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon fiber membrane materials, and in particular relates to a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure, and a preparation method and application thereof. Background Art

[0002] Transition metal phosphides (TMPs) have attracted extensive attention in the field of new energy due to their excellent electrocatalytic performance and low cost. However, their nanoparticles face challenges in conductivity and stability in their applications. In order to meet these challenges, researchers have proposed a solution to coat TMPs nanoparticles with carbon nanofibers (CNFs). Among the many coating materials, CNF stands out for its excellent conductivity, large specific surface area and excellent chemical stability. Through CNF coating, not only the conductive properties of the material are significantly improved, but also the stability and durability are improved.

[0003] The patent application with publication number CN112928287A discloses a N, P dual-doped carbon fiber loaded CoP composite catalytic material and its preparation method and application. The material is prepared by mixing ZIF-67 organic solution and polyacrylonitrile organic solution to obtain a spinning precursor solution; electrostatic spinning the spinning precursor solution to obtain a flexible film; pre-oxidizing the flexible film to obtain a pre-oxidation product; mixing the pre-oxidation product with red phosphorus, and pyrolyzing it in a protective atmosphere to obtain the N, P dual-doped carbon fiber loaded CoP composite catalytic material. The application field of this technology is oxygen reduction, and no Co / CoP heterojunction is formed, lacking a strong synergistic relationship between the two; at the same time, no hollow structure is formed, which is not conducive to the exposure of electroactive sites. Summary of the invention

[0004] The purpose of the present invention is to provide a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure and its preparation method and application. The present invention successfully forms a hollow structure as a precursor through tannic acid etching technology, and then uses electrospinning technology to form carbon nanofibers. Finally, through heat treatment and phosphating processes, a heterostructure Co / CoP is constructed. The combination of the hollow Co / CoP heterostructure and the carbon nanofiber structure enables H-Co / CoP@CNF to exhibit excellent HER catalytic performance.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] The present invention first provides a method for preparing a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure, comprising:

[0007] Step 1: Preparation of hollow H-ZIF-67;

[0008] Step 2: Add polyacrylonitrile to the hollow H-ZIF-67 prepared in step 1, and prepare the H-ZIF-67 fiber membrane by electrospinning;

[0009] Step 3: Place the H-ZIF-67 fiber membrane obtained in step 2 in a tubular furnace and heat it to obtain H-Co@CNF; place sodium hypophosphite powder upstream of the tubular furnace and H-Co@CNF downstream of the tubular furnace, and heat it under the flow of argon to obtain a flexible carbon fiber membrane H-Co / CoP@CNF based on a hollow Co / CoP heterostructure.

[0010] Preferably, the step 1 of preparing hollow H-ZIF-67 is specifically as follows:

[0011] Step 1): Cobalt nitrate and hexadecyltrimethylammonium bromide are mixed in deionized water to form a uniform solution, and the uniform solution is added to a 2-methylimidazole solution and stirred to obtain ZIF-67;

[0012] Step 2): The ZIF-67 prepared in step 1) is dispersed in a solvent, and then a tannic acid aqueous solution is added and stirred to obtain a hollow H-ZIF-67.

[0013] Preferably, the mass ratio of the cobalt nitrate, hexadecyltrimethylammonium bromide and tannic acid is 291:(5-15):(150:300).

[0014] Preferably, the particle size of ZIF-67 prepared in step 1) is 250 nm.

[0015] Preferably, the mass ratio of the hollow H-ZIF-67 and polyacrylonitrile described in step 2 is 1:1.

[0016] Preferably, the setting conditions of the electrospinning in step 2 are: the distance between the nozzle and the collector is fixed at 18 cm, the DC high voltage is adjusted to 18 kV, and the liquid feeding speed is 1 mL / h.

[0017] Preferably, in step three, the H-ZIF-67 fiber membrane is placed in a tubular furnace, heated to 200-300°C at a heating rate of 1-5°C / min under air, and maintained for 1.5-2.5h, and then heated to 800-1000°C at a heating rate of 1-5°C / min under argon protection, and maintained for 2-4h to obtain H-Co@CNF.

[0018] Preferably, in step three, under argon flow, the temperature is raised to 300-400° C. at a heating rate of 1-5° C. / min and maintained for 1-3 h to obtain H-Co / CoP@CNF.

[0019] The present invention also provides a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure obtained by the above preparation method.

[0020] The present invention also provides application of the above-mentioned hollow Co / CoP heterostructure-based flexible carbon fiber membrane in the field of electrocatalysis.

[0021] Beneficial effects of the present invention

[0022] The present invention provides a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure and its preparation method and application. The fiber membrane first successfully forms a hollow structure as a precursor through tannic acid etching technology, and then uses electrospinning technology to form carbon nanofibers. Finally, through heat treatment and phosphating processes, a heterostructure Co / CoP is constructed, aggregated to form a cage structure, and highly dispersed and densely encapsulated in carbon nanofibers. The hollow structure and the network structure formed by carbon nanofibers give the material a large specific surface area. The combination of the heterostructure Co / CoP and the porous hollow carbon nanofiber structure makes H-Co / CoP@CNF show excellent HER catalytic performance. Through a series of electrochemical characterization techniques, the results show that in an alkaline environment, 10mA cm -2 At a current density of 1.3 Å, the HER overpotential is 106 mV and the Tafel slope is 61.88 mV dec. -1 , C dl 29.97 mF cm -2 , showing good HER electrocatalytic performance. Combined with XRD, XPS, SEM and other characterizations, it is proved that the hollow structure and the network structure formed by carbon nanofibers can effectively increase the electrochemical active area and the exposure of active sites. The ECSA value of the material is 749.3cm 2 , which is higher than that of Pt / C electrode. These characteristics jointly enhance the electrocatalytic HER activity of the material and ensure the stability of the catalytic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 SEM images of ZIF-67 prepared in Example 1 and Comparative Example 1;

[0024] Figure 2 The SEM images of different H-ZIF-67 of Example 1, Comparative Examples 2 and 3;

[0025] Figure 3 X-ray diffraction patterns of ZIF-67 and H-ZIF-67 prepared in Example 1 of the present invention;

[0026] Figure 4 This is the SEM image of H-CoP / Co2P prepared in Comparative Example 4 after calcination;

[0027] Figure 5SEM images of Co / CoP@CNF prepared in Comparative Example 4 and H-Co / CoP@CNF prepared in Example 1;

[0028] Figure 6 This is the SEM-EDS image of the H-Co / CoP@CNF sample prepared in Example 1 of the present invention;

[0029] Figure 7 XRD patterns of H-Co / CoP@CNF and H-Co@CNF prepared in Example 1 and H-CoP / Co2P and Co / CoP@CNF prepared in Comparative Example 4;

[0030] Figure 8 This is the full XPS spectrum of the H-Co / CoP@CNF sample prepared in Example 1 of the present invention;

[0031] Fig. 9 The electrocatalytic performance diagram of H-Co / CoP@CNF prepared in Example 1 and H-CoP / Co2P and Co / CoP@CNF prepared in Comparative Example 4;

[0032] Fig.10 CV curves of H-Co / CoP@CNF prepared in Example 1 and H-CoP / Co2P and Co / CoP@CNF prepared in Comparative Example 4;

[0033] Fig.11 CV images of H-Co / CoP@CNF prepared in Example 1 and H-CoP / Co2P and Co / CoP@CNF prepared in Comparative Example 4 at different scanning rates:

[0034] Fig.12 SEM images of H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4 prepared in Comparative Example 5;

[0035] Fig.13 XRD patterns of H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4 prepared in Comparative Example 5;

[0036] Fig.14 HER electrochemical performance diagram of H-Co / CoP@CNF prepared in Example 1 and H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4 prepared in Comparative Example 5;

[0037] Fig.15 CV curves of H-Co / CoP@CNF prepared in Example 1 and H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4 prepared in Comparative Example 5 at different scan rates. DETAILED DESCRIPTION

[0038] The present invention first provides a method for preparing a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure, comprising:

[0039] Step 1: Prepare hollow H-ZIF-67; the specific method is preferably:

[0040] Step 1): Cobalt nitrate (Co(NO3)2·6H2O) and hexadecyltrimethylammonium bromide (CTAB) are mixed in deionized water to form a uniform solution, and the uniform solution is added to a 2-methylimidazole solution and stirred. The stirring temperature is preferably room temperature, and the stirring time is preferably 2-4 hours. Finally, the product is collected by centrifugation, and washed three times with water and ethanol respectively, and dried to obtain ZIF-67; the mass ratio of the cobalt nitrate, hexadecyltrimethylammonium bromide and 2-methylimidazole is preferably 291: (5-15): 4.54, more preferably 291: 15: 4.54; the particle size of the ZIF-67 is preferably 250nm;

[0041] Step 2): Dispersing the ZIF-67 prepared in step 1 into a solvent, wherein the solvent is preferably ethanol, and the ultrasonic dispersion time is preferably 20-40 min, then adding a tannic acid aqueous solution and stirring, wherein the stirring time is preferably 5-20 min, collecting the product by centrifugation, washing it three times with ethanol, and drying it to obtain hollow H-ZIF-67, wherein the mass ratio of hexadecyltrimethylammonium bromide to tannic acid is preferably (5-15):(150-300), and more preferably 15:300;

[0042] Step 2: Add polyacrylonitrile to the hollow H-ZIF-67 prepared in step 1, specifically: first dissolve the hollow H-ZIF-67 in step 1 in N,N-dimethylformamide (DMF), and perform ultrasonic treatment, wherein the ultrasonic treatment time is preferably 20-40 min to form a uniform solution, add polyacrylonitrile (PAN) to the above solution, and stir overnight at room temperature, inject the obtained viscous liquid into a 10 mL syringe, fix the distance between the nozzle and the collector to 18 cm, adjust the DC high voltage to 18 kV, and form a spinning membrane by electrospinning at a liquid feed rate of 1 mL / h; the mass ratio of the hollow H-ZIF-67 and polyacrylonitrile is preferably 1:1.

[0043] Step 3: Place the H-ZIF-67 fiber membrane obtained in step 2 in a tubular furnace, preferably first heating it to 200-300°C at a heating rate of 1-5°C / min under air, and keep it for 1.5-2.5h to improve the thermal stability of the fiber membrane, then heat it to 800-1000°C at a heating rate of 1-5°C / min under argon protection, and keep it for 2-4h to obtain H-Co@CNF; place sodium hypophosphite powder upstream of the tubular furnace, and place H-Co@CNF downstream of the tubular furnace, preferably heating it to 300-400°C at a heating rate of 1-5°C / min under argon flow, and keep it for 1-3h to obtain a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure H-Co / CoP@CNF.

[0044] The present invention also provides a flexible carbon fiber membrane based on a hollow Co / CoP heterostructure obtained by the above preparation method.

[0045] The present invention also provides application of the above-mentioned hollow Co / CoP heterostructure-based flexible carbon fiber membrane in the field of electrocatalysis.

[0046] The present invention is further described below with reference to specific examples, in which the raw materials involved are all commercially available.

[0047] Example 1

[0048] (1) Preparation of H-ZIF-67 cubes

[0049] 291 mg of cobalt nitrate (Co(NO3)2·6H2O) and 15 mg of hexadecyltrimethylammonium bromide (CTAB) were mixed in 20 mL of deionized water and ultrasonically dispersed to form a uniform solution A. At the same time, 4.54 g of 2-methylimidazole was ultrasonically dispersed in 140 mL of deionized water, marked as solution B. Subsequently, solution A was quickly poured into solution B under magnetic stirring and stirred for 3 h at room temperature. The product was collected by centrifugation, washed three times with water and ethanol respectively, and dried to obtain ZIF-67.

[0050] The prepared ZIF-67 cubes were dispersed in 150 mL of ethanol and ultrasonically dispersed for 30 min. Under stirring, 150 mL of an aqueous solution containing 300 mg of tannic acid was added to the above solution. After stirring for 10 min, the product was collected by centrifugation, washed three times with ethanol, and dried to obtain hollow H-ZIF-67.

[0051] (2) Preparation of H-ZIF-67 fiber membrane

[0052] 0.3g H-ZIF-67 was dissolved in 3mL N,N-dimethylformamide (DMF) and ultrasonicated for 30min to form a uniform solution. Subsequently, 0.3g polyacrylonitrile (PAN) was added to the above solution and stirred overnight at room temperature. The obtained viscous liquid was injected into a 10mL syringe, the distance between the nozzle and the collector was fixed at 18cm, the DC high voltage was adjusted to 18kV, and the spinning membrane was made by electrospinning at a liquid feeding speed of 1mL / h.

[0053] (3) Preparation of H-Co / CoP@CNF

[0054] The above H-ZIF-67 fiber membrane was placed in a tubular furnace, first heated to 250°C at a heating rate of 1°C / min under air, and maintained for 2h to improve the thermal stability of the fiber membrane. Subsequently, it was heated to 900°C at a heating rate of 2°C / min under argon protection and maintained for 3h to obtain H-Co@CNF. Finally, 2g of sodium hypophosphite (NaH2PO2) powder was placed upstream of the tubular furnace, and H-Co@CNF was placed downstream of the tubular furnace. Under the flow of argon, the temperature was raised to 350°C at a heating rate of 2°C / min and maintained for 2h to obtain H-Co / CoP@CNF.

[0055] Through X-ray diffraction (XRD), such as Figure 3 , are X-ray diffraction patterns of ZIF-67 and H-ZIF-67 prepared in Example 1 of the present invention. Analysis of the crystal structure shows that the diffraction peaks of H-ZIF-67 and ZIF-67 are substantially the same, and tannic acid etching does not change the structure of ZIF. During the etching process, although the hollow structure is etched, some interactions and surface modifications occur, but the overall skeleton and main structural features of ZIF are maintained.

[0056] In order to clarify the element distribution on the sample surface, the sample was tested using the EDS test provided by the scanning electron microscope. The EDS element spectrum of the sample is as follows: Figure 6 As shown in the figure, C, Co, P, N and O elements coexist and are evenly distributed in the composite material, indicating that the material has successfully achieved P, N and O doping. The above characterization results preliminarily confirmed the successful synthesis of the hollow Co / CoP heterostructure nanofiber composite material from the perspective of morphology and element distribution.

[0057] The H-Co / CoP@CNF prepared in Example 1 was subjected to XPS test, as shown in Table 1 and Figure 8 As shown, Figure 8 (a) represents the full XPS spectrum of H-Co / CoP@CNF; Figure 8 (b) represents Co 2p, Figure 8 (c) represents C1s, Figure 8 (d) represents P 2p, Figure 8 (f) represents O1s, high-resolution XPS spectrum. The XPS full spectrum scan results show that H-Co / CoP@CNF contains P (6.53at%), C (79.67at%), N (1.72at%), O (7.26at%) and Co (4.82at%) elements, and no other impurity elements are detected. In order to study the chemical state of the elements, the high-resolution XPS spectra of Co 2p, C 1s, P 2p, and O 1s were detected. The Co 2p spectrum shown in the figure, the peaks at about 778.4eV, 781.3eV, 792.9eV and 797.4eV are attributed to Co(0), Co 2+ / 3+ , Co(0) and Co 2+ / 3+ , the two peaks at about 785.5eV and 803.2eV are satellite peaks. For the high-resolution XPS spectrum of C1s, the peaks at 284.6, 285.2, 286.2, and 288.4eV are attributed to CC / C=C, CP, CO, and O=CO, respectively. For the high-resolution XPS spectrum of P 2p, the peaks at 129.6eV, 130.5eV, and 133.9eV are attributed to P 2p 3 / 2 、P 2p 1 / 2 and PC. This indicates that the P element not only combines with Co to form the Co-P bond in CoP, but is also doped into the CNF structure to form the PC bond. In general, the XPS results further confirm the composition and structure of the hollow Co / CoP heterostructured nanofibers. It also confirms that electrocatalytic active sites such as Co, Co-P, and PC are formed in H-Co / CoP@CNF, which will be beneficial for the composite material to obtain excellent catalytic performance.

[0058] Table 1 Element contents of C, Co, P, O and N in H-Co / CoP@CNF determined by XPS

[0059] element C Co P O N Content (at%) 79.67 4.82 6.53 7.26 1.72

[0060] Comparative Example 1

[0061] 291 mg of cobalt nitrate (Co(NO3)2·6H2O) was mixed with 0 mg and 5 mg of hexadecyltrimethylammonium bromide (CTAB) in 20 mL of deionized water, and ultrasonic dispersion was performed to form a uniform solution A. At the same time, 4.54 g of 2-methylimidazole was ultrasonically dispersed in 140 mL of deionized water, which was marked as solution B. Subsequently, solution A was quickly poured into solution B under magnetic stirring and stirred for 3 h at room temperature. The product was collected by centrifugation, washed three times with water and ethanol respectively, and dried to obtain ZIF-67.

[0062] The morphology of ZIF-67 prepared in Example 1 and Comparative Example 1 was characterized. Figure 1 As shown in the figure, ZIF-67 without the addition of surfactant CTAB is composed of larger particles with a diameter of 500nm. The particles are unevenly hemispherical, with rough edges. The particles are arranged very closely, with a small distance between each other, and there is no obvious arrangement pattern. When the 5mg CTAB group is added, it can be found that the crystal morphology changes from a hemisphere to a cube with a side length of 500nm. The shape of the cube becomes more regular, the edge becomes smoother, and the arrangement between the particles is more orderly, but there are a few cubes with small size and incomplete shape. The group with the addition of 15mg CTAB is composed of cubes with a side length of about 250nm. The morphology of the cube is further improved, the shape is more regular, the size is more uniform, and the arrangement is more neat. This shows that the addition of CTAB can not only change the morphology of the crystal but also control the size of the crystal. Therefore, this study can further control the size and morphology of the crystal by controlling the amount of surfactant added.

[0063] The reasons why surfactant CTAB promotes the formation of ZIF-67 cubes are as follows:

[0064] (1) Template effect: The amphiphilic properties of CTAB enable it to self-assemble into various aggregates, such as micelles, vesicles, liquid crystals, etc. These aggregates can act as templates to guide the nucleation and growth direction of ZIF-67 nanocrystals, control the size and shape of nanocrystals, and thus promote the formation of a cubic structure of ZIF-67.

[0065] (2) Charge effect: The cationic part of the CTAB molecule can interact electrostatically with the anionic part of ZIF-67 (such as the nitrogen atom on the imidazole ring). This charge effect helps the ZIF-67 crystal grow along a specific direction, thereby forming a cubic structure.

[0066] (3) Surface tension: CTAB can also reduce the surface tension between the aqueous phase and the organic phase, making it easier to form uniform ZIF-67 nanocrystals at the interface between the two phases. This reduction in surface tension helps the crystals grow in a more regular direction, thus forming a cubic structure.

[0067] (4) Capping agent effect: CTAB, as a capping agent, effectively reduces the crystal surface energy through dipole-dipole interaction or van der Waals force, thereby reducing the total energy of the system, thereby finely controlling crystal growth and promoting the formation of various morphologies. The key is that the hydrophobic hydrocarbon chain of CTAB can adsorb on the surface of ZIF-67 crystals in aqueous solution, especially those hydrophobic regions, effectively acting as a capping agent to slow down the growth rate of crystals. Due to the adsorption of CTAB, the growth rate of certain crystal faces is inhibited, resulting in the inhomogeneity of the growth rate of different crystal faces, and ultimately causing changes in the crystal morphology.

[0068] As the concentration of CTAB added varies, the concentration adsorbed on the crystal surface will also change, which will inhibit the growth of the crystal to varying degrees. Figure 1 It can be seen that as the concentration of CTAB increases, the size of the final crystals gradually decreases. The surfactant CTAB controls the size and morphology of the crystals by regulating the nucleation rate and crystal growth rate. The capping agent can reduce the supersaturation potential of the monomer and promote the formation of nuclei, thereby generating smaller crystals. At the same time, the capping agent can also inhibit the crystal growth rate and further control the crystal morphology. As the amount of CTAB added increases, its concentration in the solution increases, which may lead to more ZIF-67 nanocrystals nucleating in a shorter time. At a high nucleation rate, substances required for crystal growth, such as metal ions and organic ligands, will be consumed faster, thereby limiting the growth of the crystal and making the particle size smaller.

[0069] The present invention regulates the particle size of ZIF-67 by regulating the amount of surfactant and the reaction time, and finally determines that the ZIF-67 with a particle size of 250nm is used as the basis for the next step of preparation. The precursor of small-size (250nm) ZIF-67 is conducive to obtaining a highly active catalyst, because the shape of the small-size precursor can be easily maintained and avoid structural damage during heat treatment, thereby causing exposure of more active sites and rapid transmission of electrons. The optimized ZIF-67 has the characteristics of high crystallinity, good dispersibility, regular morphology, uniform size, and high experimental repetition success rate.

[0070] Comparative Example 2

[0071] The preparation method and conditions are the same as those in Example 1 (1), except that 150 mg of tannic acid is added to obtain H-ZIF-67.

[0072] Comparative Example 3

[0073] The preparation method and conditions were the same as those in Example 1 (1), except that 5 mg of CTAB and 150 mg and 300 mg of tannic acid were added to obtain H-ZIF-67.

[0074] Using ZIF-67 with a particle size of 250 nm as a precursor, tannic acid (TA) was used as a surface functionalization and etching agent to hollow out the cube to obtain a hollow structure, which was denoted as H-ZIF-67. In order to explore the effect of tannic acid content on the sample morphology, samples of different H-ZIF-67 in Example 1, Comparative Example 2 and 3 were prepared by controlling the amount of tannic acid added, and SEM tests were performed on them. Figure 2 ,in Figure 2 (a) represents the addition of 5 mg CTAB and 150 mg tannic acid; Figure 2(b) represents the addition of 5 mg CTAB and 300 mg tannic acid; Figure 2 (c) represents the addition of 15 mg CTAB and 150 mg tannic acid; Figure 2 (d) represents the addition of 15 mg CTAB, 300 mg tannic acid, Figure 2 The hollow yolk shell structure can be clearly seen. When a small amount of tannic acid is added, the interior of the ZIF-67 cube does not fully reach the expected etching degree, the etching depth is insufficient, and the material exhibits an uneven etching effect. 300 mg of tannic acid etches completely uniformly. When constructing a metal-organic framework (MOF), the introduction of mesoporous or macroporous structures by etching can enable electrons to maintain a high degree of freedom inside the MOF, while promoting the diffusion efficiency of substrates and products. In this process, tannic acid (TA) plays a dual role. On the one hand, it releases hydrogen ions (H + ) can be used to etch MOF, thereby forming the desired mesoporous or macroporous structure inside; on the other hand, TA can wrap around the outside of MOF, providing a layer of protection, effectively preventing the MOF structure from collapsing during the etching process. This method is not only simple and easy, but also low in cost and time, providing a new idea for the customized design and functional application of MOF materials.

[0075] Comparative Example 4

[0076] In order to verify the influence of composition and structure on the composite material, non-phosphated H-ZIF-67 spinning membrane, phosphated H-ZIF-67, and phosphated ZIF-67 spinning membrane were synthesized and named H-Co@CNF, H-CoP / Co2P, and Co / CoP@CNF, respectively.

[0077] The preparation method of H-CoP / Co2P is as follows:

[0078] 1) Prepare hollow H-ZIF-67 in the same manner as step (1) of Example 1:

[0079] 2) The above hollow H-ZIF-67 powder was directly placed in a tube furnace, first heated to 250°C at a heating rate of 1°C / min under air, and maintained for 2 hours. Subsequently, it was heated to 900°C at a heating rate of 2°C / min under argon protection and maintained for 3 hours. Finally, 2g of sodium hypophosphite (NaH2PO2) powder was placed upstream of the tube furnace, and H-ZIF-67 was placed downstream of the tube furnace. Under argon flow, the temperature was raised to 350°C at a heating rate of 2°C / min and maintained for 2 hours to obtain H-CoP / Co2P.

[0080] The preparation method of Co / CoP@CNF is as follows:

[0081] 1) Prepare ZIF-67 in the same manner as step (1) of Example 1;

[0082] 2) Adding polyacrylonitrile to the ZIF-67 prepared above, specifically: first dissolving 0.3 g of ZIF-67 in N,N-dimethylformamide (DMF), ultrasonically treating for 30 min to form a uniform solution, adding 0.3 g of polyacrylonitrile (PAN) to the above solution, and stirring at room temperature overnight, injecting the obtained viscous liquid into a 10 mL syringe, the distance between the nozzle and the collector is fixed at 18 cm, the DC high voltage voltage is adjusted to 18 kV, and the ZIF-67 spinning membrane is prepared by electrospinning at a liquid feeding speed of 1 mL / h;

[0083] 3) The ZIF-67 fiber membrane was placed in a tube furnace, first heated to 250°C at a heating rate of 1°C / min under air, and maintained for 2 hours to improve the thermal stability of the fiber membrane. Subsequently, it was heated to 900°C at a heating rate of 2°C / min under argon protection and maintained for 3 hours. Finally, 2g of sodium hypophosphite (NaH2PO2) powder was placed upstream of the tube furnace, and the sample was placed downstream of the tube furnace. Under argon flow, the temperature was raised to 350°C at a heating rate of 2°C / min and maintained for 2 hours to obtain Co / CoP@CNF.

[0084] like Figure 4 The SEM image of H-CoP / Co2P after calcination is depicted. After phosphating and calcining, the nanocube structure of H-ZIF-67 is destroyed and serious aggregation occurs. This structure is not conducive to the exposure of active sites, affects the electron transport ability of the material, and reduces the catalytic performance of the material. This is because without the coating of carbon nanofibers, the CoP / Co2P nanoparticles have serious aggregation.

[0085] Through SEM pictures, Figure 5 , characterized the microstructure of Co / CoP@CNF and H-Co / CoP@CNF, where Figure 5 (a) represents Co / CoP@CNF before calcination; Figure 5 (b) represents H-Co / CoP@CNF before calcination; Figure 5 (c) represents Co / CoP@CNF after calcination; Figure 5(d) represents H-Co / CoP@CNF after calcination, in which H-ZIF-67 nanocubes are highly dispersed and densely encapsulated in one-dimensional continuous carbon nanofibers. The carbon nanofibers are uniformly bamboo-shaped and intertwined to form a three-dimensional network. After calcination, the fiber structure is well maintained, and the nanoparticles are aggregated into a cubic cage structure and densely encapsulated in the carbon nanofibers. This structure not only ensures the stability and dispersibility of the nanoparticles, but also effectively utilizes the excellent conductivity and large specific surface area of ​​carbon nanofibers, providing a possibility for improving the performance of the composite material. However, the ZIF-67 in the Co / CoP@CNF group is unevenly dispersed, with a large number of aggregates. After calcination, the fibers are not well maintained and are destroyed, and the nanoparticles are exposed to the outside. When the nanoparticles are exposed to the external environment, they will inevitably come into direct contact with the electrolyte. This direct interaction significantly weakens the durability and stability of the composite material under harsh reaction environments.

[0086] Figure 7The XRD patterns of H-Co / CoP@CNF and H-Co@CNF prepared in Example 1 and H-CoP / Co2P and Co / CoP@CNF prepared in Comparative Example 4 were used to explore the physical composition of the synthesized samples. The prepared sample H-Co / CoP@CNF was compared with the standard comparison card of CoP (PDF#29-0497). The diffraction peaks of CoP appeared at 2θ of 31.6°, 35.336°, 36.696°, 46.233°, 48.13°, 56.027° and 56.781°, and the corresponding crystal planes were (011), (200), (102), (112), (211), (020) and (301), respectively. The prepared sample was compared with the standard comparison card of Co (PDF#15-0806), and the diffraction peaks of Co appeared at 2θ of 44.216° and 51.522°, corresponding to the crystal planes (111) and (200), respectively. During the phosphating of H-Co / CoP@CNF, due to the protection of CNF coating, H-ZIF-67 was partially phosphated, thereby retaining part of the original Co structure, and Co and CoP formed a heterogeneous structure. The unphosphated H-Co@CNF only showed diffraction peaks corresponding to the Co crystal phase at 44.216°, 51.522° and 75.853°. H-CoP / Co2P is the phosphating of H-ZIF-67, and only CoP / Co2P phases are generated, indicating that under this condition, H-ZIF-67 is completely phosphated without CNF coating protection, and almost all Co is converted into phosphide. Co / CoP@CNF is the phosphating of ZIF-67 spinning membrane, generating Co peak and CoP peak. Since ZIF-67 itself has a solid structure, the Co element rich in it still maintains a high content after phosphating, so the Co peak is relatively strong in the formed composite material. From the XRD spectrum, no obvious impurity peaks or peak position shifts were found, indicating that the phase purity obtained in the experiment is very high and there are no other impurities. Based on the above analysis, the following conclusions can be drawn: CNF coating protection plays a key role in the phosphating process, which can affect the phosphating degree of ZIF-67 and then regulate the phase composition of the final product. Co / CoP heterostructures may have unique physical and chemical properties, such as enhanced electrochemical performance and catalytic activity, and have potential application value.

[0087] In order to verify the electrocatalytic material performance of each sample, LSV test was performed on each sample. The test results are shown in Fig. 9 As shown, Fig. 9 (a) is the LSV curve of different samples. Fig. 9 (b) is the relationship between overpotential and current density of different samples; Fig. 9(c) is the Tafel slope of different samples. It can be seen from the figure that H-Co / CoP@CNF exhibits the best HER activity except Pt / C and exceeds Pt / C at high current. -2 At a current density of , the HER overpotential is 106 mV, showing excellent HER activity. Although there is a Co / CoP heterostructure in Co / CoP@CNF, it does not have a hollow structure, so its HER activity is inferior to H-Co / CoP@CNF. Although H-CoP / Co2P has a hollow structure, it exhibits the worst HER activity due to complete phosphating and the lack of carbon nanofibers covering the 3D structure. These indicate that the Co / CoP heterostructure, the one-dimensional continuous CNF structure, and the porous and hollow combined structure have enhanced electrochemical properties and catalytic activity. H-Co / CoP@CNF has excellent HER performance due to its large specific surface area and more active sites. Further analysis shows that the Tafel slope of the catalyst can show the kinetics of the hydrogen evolution process. The Tafel slope calculated from the LSV results is as follows Fig. 9 As shown in (c), the Tafel slope of H-Co / CoP@CNF is 61.88 mV dec. -1 , which is higher than Co / CoP@CNF (87.47mV dec -1 ) and H-CoP / Co2P (117.08mV dec -1 ) is lower. This further shows that H-Co / CoP@CNF has good HER catalytic activity.

[0088] Fig.10 The CV curves of different samples at different scan rates are given. Fig.10 (a) represents H-Co / CoP@CNF, Fig.10 (b) represents Co / CoP@CNF, Fig.10 (c) represents H-CoP / Co2P, Fig.10 (d) represents Pt / C. The CV results were analyzed to obtain the double layer capacitance (C dl Due to the hollow structure and the high specific surface area of ​​the network structure formed by carbon nanofibers, H-Co / CoP@CNF shows a high electrochemical active area, C dl 29.97 mF cm -2 , ECSA value is 749.3cm 2, higher than that of Pt / C electrode. At the same time, in order to further explore the intrinsic activity of the active sites of the samples, the LSV curves were normalized to the corresponding ECSA. Comparing the curves of H-Co / CoP@CNF with Co / CoP@CNF and H-CoP / Co2P, it can be found that the former shows higher activity in electrochemical tests not only because of the higher electrochemical active area, but also because of its higher intrinsic activity. In summary, the reason why H-Co / CoP@CNF exhibits excellent catalytic activity comparable to that of Pt / C under alkaline conditions is due to the high intrinsic activity of its active sites, the high electrochemical active area of ​​the carbon nanofiber substrate, and the good conductivity. The excellent performance of this catalyst provides broad prospects for its application in fuel cells, water electrolysis and hydrogen production.

[0089] Fig.11 are CV images of different samples at different scanning rates: Fig.11 (a) Relationship between current density and scan rate; Fig.11 (b) Specific ESCA value for each sample; Fig.11 (c) ECSA normalized LSV curve; Fig.11 (d) Electrochemical impedance spectroscopy of different samples, by measuring EIS, such as Fig.11 (d) to study the catalytic kinetics. The corresponding equivalent circuit is shown in the inset, where R s Represents the electrolyte resistance, R ct is the charge transfer resistance, and CPE is the constant phase element of the double electric layer. The impedance value can be obtained by fitting the equivalent circuit. According to the results, it can be found that different samples have similar R s Compared with Co / CoP@CNF and H-CoP / Co2P samples, the R ct The smallest value indicates a more efficient charge transfer performance.

[0090] Comparative Example 5

[0091] The steps and conditions are the same as those in Example 1, except that in step (2), the amounts of H-ZIF-67 added are 0.200 g and 0.400 g, respectively, to finally obtain H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4.

[0092] In order to explore the effect of metal content on the samples, SEM tests were performed on the H-Co / CoP@CNF prepared in Example 1 and H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4 prepared in Comparative Example 5. Fig.12 , Fig.12 (a) represents H-Co / CoP@CNF-2 before calcination; Fig.12(b) represents H-Co / CoP@CNF-4 before calcination; Fig.12 (c) represents H-Co / CoP@CNF-2 after calcination; Fig.12 (d) represents H-Co / CoP@CNF-4 after calcination. It can be seen that with the increase in the amount of H-ZIF-67 added, the H-ZIF-67 cubes in the spinning film aggregate, which will hinder the exposure of active sites and reduce the catalytic performance of the material. More seriously, when the amount of H-ZIF-67 added exceeds a certain range, the carbon nanofiber structure after calcination may be destroyed. These results show that the content of H-ZIF-67 in H-Co / CoP@CNF composites is crucial for the formation of uniform and moderate CNF.

[0093] In order to deeply analyze the influence of metal content on the material phase, XRD test was used to explore the structural characteristics of H-Co / CoP@CNF composite materials, such as Fig.13 . By comparing the XRD spectra of different samples, the following phenomena were found. First, in the XRD spectrum of the H-Co / CoP@CNF-2 sample, the diffraction peak of CoP is abnormally strong, which indicates that even under the protection of carbon nanofibers, due to the small amount of H-ZIF-67 added, the material still forms a large amount of CoP phase during the phosphating process. This phenomenon may be attributed to the high conversion rate of H-ZIF-67 during the phosphating process, which provides a rich cobalt source for the formation of CoP. Further observation of the H-Co / CoP@CNF-4 sample shows that although it also has the protection of CNF, due to the large amount of H-ZIF-67 added, the structure of CNF may be destroyed during the calcination process, resulting in a further increase in the amount of CoP generated. This may be because more H-ZIF-67 provides more cobalt sources, thereby promoting the formation of more CoP during the phosphating process.

[0094] Adjusting the ratio of H-ZIF-67 to polyacrylonitrile (PAN) in the H-ZIF-67 spinning membrane can significantly affect the phase composition of the material. By precisely controlling this ratio and optimizing the phosphating conditions, the present invention can not only achieve precise control of the phase of the final product, but also adjust other physical and chemical properties of the material, such as conductivity, specific surface area and catalytic activity. This regulation ability is of great significance for the development of composite materials with specific performance requirements.

[0095] The samples with different metal contents in Example 1 and Comparative Example 5 were subjected to HER electrochemical tests, and the linear sweep voltammetry (LSV) test results revealed obvious differences in activity between the samples, such as Fig.14 As shown, Fig.14 (a) is the LSV graph, Fig.14 (b) is the corresponding Tafel slope, Fig.14 (c) is a graph showing the relationship between overpotential and current density. The LSV curve shows that the H-Co / CoP@CNF sample exhibits better HER activity than H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4. This phenomenon may be attributed to the specific ratio of H-ZIF-67 and PAN in the H-Co / CoP@CNF sample and the maintenance of the integrity of carbon nanofibers (CNF) during the calcination process. The CNF structure of the H-Co / CoP@CNF-4 sample was damaged during the calcination process, resulting in a significant decrease in its HER activity, making it the worst among the three. The HER activity of H-Co / CoP@CNF-2 is between the two, indicating that the optimization of metal content and structure is crucial to improving the electrochemical performance of the material. Further analysis was confirmed by the calculation of the Tafel slope. Fig.14 The Tafel slope results shown in Figure 2 show that the Tafel slope of H-Co / CoP@CNF is 61.88 mV dec. -1 , which is significantly lower than that of H-Co / CoP@CNF-4 and H-Co / CoP@CNF-2. A lower Tafel slope is usually associated with a faster electrochemical reaction rate, which further confirms that the H-Co / CoP@CNF sample has better HER catalytic activity.

[0096] Fig.15 The CV curves of different samples at different scan rates are given. Fig.15 (a) CV images of H-Co / CoP@CNF-2 at different scanning rates. Fig.15 (b) CV images of H-Co / CoP@CNF-4 at different scanning rates. Fig.15 (c) is the relationship between current density and scan rate. Fig.15 (d) is the LSV curve normalized by ECSA. Fig.15 (e) The specific ESCA value for each sample. It can be seen that compared with H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4, the C dl To 29.97mF cm -2, representing its larger electrochemically active surface area (ECSA). At the same time, the LSV curve was normalized to the corresponding ECSA, and the intrinsic activity of H-Co / CoP@CNF was also higher. It can be seen that the metal content has a great influence on the morphology and electrocatalytic performance of H-Co / CoP@CNF, among which the H-ZIF:PAN=3:3 group showed the best performance. This optimized metal content and structure not only improves the conductivity of the material, but also enhances its ability to catalyze HER by providing more active sites and improving the charge transfer process. In summary, the electrochemical performance of H-Co / CoP@CNF composites can be optimized by precisely controlling the ratio of H-ZIF-67 to PAN. These findings provide important guidance for the design and optimization of electrocatalysts. The electrochemical performance of the material can be significantly improved by precisely controlling the metal content and structure.

[0097] In summary, the present invention successfully formed a hollow structure as a precursor through tannic acid etching technology. Then, the electrospinning technology was used to form carbon nanofibers. Finally, the heterostructured Co / CoP was constructed through heat treatment and phosphating process. The combination of heterostructured Co / CoP and porous hollow carbon nanofiber structure makes H-Co / CoP@CNF show excellent HER catalytic performance. Through a series of electrochemical characterization techniques, including cyclic voltammetry (CV), linear sweep voltammetry (LSV), electrochemical impedance spectroscopy (EIS), etc., different materials such as H-Co / CoP@CNF, H-Co@CNF, H-CoP / Co2P, Co / CoP@CNF, etc. were compared in detail. In an alkaline environment, 10mA cm -2 At a current density of , the HER overpotential is 106mV and the Tafel slope is 61.88mVdec -1 , C dl 29.97 mF cm -2 , showing good HER electrocatalytic performance. In addition, samples with different metal contents, including H-Co / CoP@CNF-2 and H-Co / CoP@CNF-4, were compared. The results consistently showed that H-Co / CoP@CNF material performed best in terms of electrocatalytic HER performance. Combined with XRD, XPS, SEM and other characterizations, it was proved that the hollow structure and the network structure formed by carbon nanofibers can effectively increase the electrochemical active area and the exposure of active sites. The ECSA value of the material is 749.3cm 2 , which is higher than that of Pt / C electrode. These characteristics jointly enhance the electrocatalytic HER activity of the material and ensure the stability of the catalytic process.

Claims

1. A method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane, characterized in that: include: Step 1: Preparation of hollow H-ZIF-67; Step 2: Add polyacrylonitrile to the hollow H-ZIF-67 prepared in step 1, and prepare the H-ZIF-67 fiber membrane by electrospinning; Step 3: Place the H-ZIF-67 fiber membrane obtained in step 2 in a tubular furnace and heat it to obtain H-Co@CNF; place sodium hypophosphite powder upstream of the tubular furnace and H-Co@CNF downstream of the tubular furnace, and heat it under the flow of argon to obtain a flexible carbon fiber membrane H-Co / CoP@CNF based on a hollow Co / CoP heterostructure.

2. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 1, characterized in that: Step 1 Preparation of hollow H-ZIF-67 is specifically as follows: Step 1): Cobalt nitrate and hexadecyltrimethylammonium bromide are mixed in deionized water to form a uniform solution, and the uniform solution is added to a 2-methylimidazole solution and stirred to obtain ZIF-67; Step 2): The ZIF-67 prepared in step 1) is dispersed in a solvent, and then a tannic acid aqueous solution is added and stirred to obtain a hollow H-ZIF-67.

3. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 2, characterized in that: The mass ratio of the cobalt nitrate, hexadecyltrimethylammonium bromide and tannic acid is 291:(5-15):(150:300).

4. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 2, characterized in that: The particle size of ZIF-67 prepared in step 1) is 250 nm.

5. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 1, characterized in that: The mass ratio of the hollow H-ZIF-67 and polyacrylonitrile described in step 2 is 1:

1.

6. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 1, characterized in that: The setting conditions of the electrospinning in step 2 are: the distance between the nozzle and the collector is fixed at 18 cm, the DC high voltage is adjusted to 18 kV, and the liquid feeding speed is 1 mL / h.

7. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 1, characterized in that: In step three, the H-ZIF-67 fiber membrane is placed in a tubular furnace, heated to 200-300°C at a heating rate of 1-5°C / min under air, and maintained for 1.5-2.5h. Subsequently, it is heated to 800-1000°C at a heating rate of 1-5°C / min under argon protection and maintained for 2-4h to obtain H-Co@CNF.

8. The method for preparing a hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 1, characterized in that: In step 3, under the flow of argon, the temperature is raised to 300-400°C at a rate of 1-5°C / min and maintained for 1-3h to obtain H-Co / CoP@CNF.

9. A flexible carbon fiber membrane based on a hollow Co / CoP heterostructure obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the hollow Co / CoP heterostructure flexible carbon fiber membrane according to claim 9 in the field of electrocatalysis.

Citation Information

Patent Citations

  • N-and-P double-doped carbon fiber-loaded CoP composite catalytic material as well as preparation method and application thereof

    CN112928287A

  • Preparation method of bubble-shaped nano-fibers embedded with cobalt phosphide nanoparticles and used for electro-catalytic hydrogen evolution

    CN114016162A

  • Cobalt-iron alloy nanoparticles based on hollow cubic carbon material as well as preparation method and application of cobalt-iron alloy nanoparticles

    CN114256470A

  • CoS2 / CoO heterojunction nanosheet three-dimensional assembled carbon nanofiber material as well as preparation method and application thereof

    CN117552187A

  • Lithium-philic site modified carbon network scaffold composite material as well as preparation method and application thereof

    CN117673326A